2003
DOI: 10.1016/s0021-9517(02)00051-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Fe species during the synthesis of over-exchanged Fe/ZSM5 obtained by chemical vapor deposition of FeCl3

Abstract: The evolution of iron in over-exchanged Fe/ZSM5 prepared via chemical vapor deposition of FeCl 3 was studied at each stage of the synthesis. Different characterization techniques (EXAFS, HR-XANES, 57 Fe Mössbauer spectroscopy, 27 Al NMR, EELS, HR-TEM, XRD, N 2 physisorption, and FTIR spectroscopy) were applied in order to correlate the changes occurring in the local environment of the Fe atoms with migration and aggregation phenomena of iron at micro-and macroscopic scale. Mononuclear isolated Fe-species are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
56
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(63 citation statements)
references
References 57 publications
5
56
0
2
Order By: Relevance
“…In the literature, this peak has been modeled as an Fe-Fe path with 0.5 e N e 1.6. 2,11,13,[24][25][26]30 The curvefit distance at 2.94 Å is 0.23 Å longer than that reported for a simple di-μ-oxo bridged compound, L 2 Fe 2 -(μ-O) 2 (L is tris(2-pyridylmethyl)amine), at 2.71 Å; 18 however, it is considerably shorter than the Fe-Fe distance in…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…In the literature, this peak has been modeled as an Fe-Fe path with 0.5 e N e 1.6. 2,11,13,[24][25][26]30 The curvefit distance at 2.94 Å is 0.23 Å longer than that reported for a simple di-μ-oxo bridged compound, L 2 Fe 2 -(μ-O) 2 (L is tris(2-pyridylmethyl)amine), at 2.71 Å; 18 however, it is considerably shorter than the Fe-Fe distance in…”
mentioning
confidence: 76%
“…18 XAFS has also proven to be a powerful tool for establishing the connectivity of the Fe species present in Fe/ZSM-5. 3,11,13 Recently, the intentional incorporation of extra-framework Al or Ga was shown to enhance greatly the activity of Fe/ZSM-5 for N 2 O decomposition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques, including FTIR, H 2 -TPR, XANES, EXAFS, Mössbauer spectroscopy, EPR and UV/Vis DRS, were used for the characterization of iron species during the CVD preparation process of Fe-ZSM-5 catalysts [30][31][32]. After FeCl 3 sublimation, iron was introduced into the zeolite, exchanging with the Brønsted protons in the form of isolated FeCl 2+ species [30][31][32].…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%
“…After FeCl 3 sublimation, iron was introduced into the zeolite, exchanging with the Brønsted protons in the form of isolated FeCl 2+ species [30][31][32]. The EXAFS fitting results revealed that the majority of Fe species formed after FeCl 3 sublimation and reaction with the Brønsted acid sites were mononuclear, and consisted of isolated tetrahedral Fe 3+ species attaching to the zeolite matrix via two oxygen atoms at the same distance.…”
Section: Chemical Vapor Deposition (Cvd)mentioning
confidence: 99%